Effective Parameters onto Graft Copolymer Based on Carboxymethyl with Acrylic Monomer - Sadeghi, Mohammad; Safari, Soudeh; Shahsavari, Hadis; Sadeghi, Hossein; Soleimani, Fatemeh (Asian Journal of Chemistry, 2013)
The effective parameters onto graft copolymer sodium carboxymethyl celloluse with acrylic monomers were performed. The graft copolymerization reaction was carried out in a homogeneous medium and by reaction of N-isopropylacrylamide (NIPAAm) and methacrylamide (MAAm) with carboxymethyl cellulose backbones. A mechanism for the graft copolymer formation was also suggested. Finally, the effect of ammonium persulfate, carboxymethyl cellulose concentration and MAAm/NIPAAm weight ratio and reaction temperature on the per cent grafting has been investigated.